Prednosti in pomanjkljivosti vrstniškega ocenjevanja - Goršak, Karmen (Vestnik za tuje jezike, 2010)
This article examines current theoretical work and research findings regarding the effectiveness of peer assessment. The main purpose of the articleis to define peer assessment and its subcategory peer feedback and to present the advantages and limitations of peer assessment derived from different research findings. In addition, conditions and strategies to successfully guarantee the benefits of peer assessment are presented. The main research studies, mentioned in this article, have been carried out in different disciplines in higher education programmes and their findings reveal positive students' and teachers' attitude to peer assessment as well as high correlation between peers' and teachers' grades. The main results of the studies show a positive effect of peer assessment on student's active role in the process of learning and assessment, the development of social and professional skills, student's autonomy, critical thinking, peer- and self-assessment skills. Recommendations for implementing peer assessment within foreign language teaching, as well as implications for future research work are provided.
Keywords: vrstniško ocenjevanje; vrstniška ocena; ocenjevanje; tuji jeziki; gimnazija